The enslaved family as reflected in Post-colonial African Drama: Ngugi and Ngugi’s I Will Marry When I Want - Bazimaziki, Gabriel; Nsengiyumva, Vedaste (International Journal of Humanities and Education Development (IJHED), 2021)
In literary studies, critics demonstrate authors’ role to depict human life using characters and themes affecting them through various literary forms viz prose fiction, poetry and drama. The latter tells a story by engaging dialogue and conflicts among characters. Driven by the didactic literary theory, the researchers carry out a literary analysis of Ngugi wa Thiong’o and Ngugi wa Mirii’s morality play “I Will Marry When I Want”; and explore the situation of an enslaved family reflected in the impossible promise of the land grabber and exploiter targeting a one and half acres of land that the family was living on. Discussion centers on character victims in the story, leading to the conclusion that the play depicts the hypocrisy and power of the elite - haves at the expense of the poor in post-colonial Africa. The Kioi’s malice unbeknown to Kiguunda’s family is one of many cases of human bad manners that affect society members due to their poor life background rooted in the effects of exploitation and oppression; resulting in the victim’s wrong choice motivated by the stopgap altogether.